Future Teachers’ Attitudes about Certain Aspects of Information and Communication Technologies - Ružić-Baf, Maja; Radetić-Paić, Mirjana; Zarevski, Predrag (2013)
The use of information and communication technologies (ICT) has an important place within the process of education. Personal computers are present in numerous households, kindergartens, and almost all primary schools. Permanent education of parents, educators and teachers about the application of ICT has an important role in the process of children's education. Familiarising children with positive and negative consequences of the application of new technologies and timely involvement of all persons involved in the process of education contributes to adequate and quality use of new technologies. In the introductory part, the paper deals with the importance of parents' role regarding the use of ICT in children's education, inadequate and excessive use of computers, playing computer games and particular modes of behaviour, and describes the American national educational technology standards for teachers and courses in the field of information and communication technology. The paper brings the research conducted at the University of Juraj Dobrila in Pula on the attitudes of future teachers and parents about their competence in applying ITC and negative consequences of excessive use of computers, that is, playing computer games. The dominant attitudes are that parents should be more familiar with the content of computer games and those teachers are not sufficiently familiar with the content of computer games, types (genres) of games and negative consequences of frequent use of computers. It is surprising that even ¼ of students have "conservative" attitude about the need of continuing education on ICT in future work.